Neutralizing Antibodies to Severe Fever With Thrombocytopenia Syndrome Virus Among Survivors, Non-Survivors and Healthy Residents in South Korea - Yoo, Jeong Rae; Kim, Jae-Yong; Heo, Sang Taek; Kim, Jihye; Park, Hyeong-Jun; Lee, Joo-Yeon; Lim, Hee-Young; Park, Woo-Jung; Cho, Nam-Hyuk; Kim, Jung Mogg; Nam, Jae-Hwan; Lee, Keun Hwa (Frontiers in Cellular and Infection Microbiology, 2021)
Sever fever with thrombocytopenia syndrome (SFTS), a newly emerging tick-borne viral disease, has been detected in Asia since 2009, and person-to-person transmission is possible. SFTS is characterized by atypical signs, including mild to severe febrile illness similar to that associated with haemorrhagic fever, with 16.2 to 30% mortality. We found that the titres of neutralizing antibodies, play an important role in protective immunity, to SFTS virus (SFTSV) in survivors and healthy residents who lived in endemic areas and who were positive for SFTSV IgG, were higher than those in non-survivor patients. Moreover, the titres were maintained in surviving patients and healthy residents but not in non-surviving patients in South Korea.